PENINGKATAN HASIL BELAJAR IPS MELALUI PENERAPAN PROBLEM BASED LEARNING BERBANTUAN MEDIA POWERPOINT - MUZAINI MUZAINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The objectives of research are: to improve social studies learning activities and social studies learning outcomes of the students of Gemolong Junior High School 1, Sragen Regency through the implementation of problem based-learning (PBL) assisted by powerpoint. This research is classroom action research (CAR). The subjects of research were students of VIIIC Gemolong Junior High School 1, Sragen regency. The actions applied were problem based-learning approaches by assisted powerpoint. The data were collected by using documentation, observation, interview, and test. In this research, the data were analyzed with descriptive statistics. This analysis was used to describe the process and the improvement of learning outcomes before and after the implementation of PBL assisted by powerpoint. The results show that after the implementation of PBL assisted by powerpoint: 1) there is improvement of social studies learning activities 57% in Cycle I and it improved 5% in Cycle II; and 2) there is improvement of cognitive learning outcomes 57,58% in Cycle I, and it improved 6,06% in Cycle II; 3) there is improvement of mastery learning 36,37% in Cycle I, and it improved 12,12% in Cycle II; and 4) improvement of attitude and teamwork skill 24,24% in Cycle II. ABSTRAKPenelitian ini bertujuan untuk meningkatkan: aktivitas pembelajaran IPS melalui penerapan problem-based learning (PBL) berbantuan powerpoint dan hasil belajar IPS siswa SMPN 1 Gemolong Kabupaten Sragen. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian adalah siswa kelas VIIIC SMPN 1 Gemolong Kabupaten Sragen. Jenis tindakan yang diterapkan adalah pembelajaran dengan pendekatan PBL berbantuan powerpoint. Teknik pengumpulan data yang digunakan adalah dokumentasi, observasi, wawancara dan tes. Data dianalisis dengan statistik deskriptif. Analisis ini untuk menjelaskan perkembangan proses pembelajaran dan hasil belajar sebelum dan setelah diterapkan pembelajaran dengan PBL. Hasil penelitian ini menunjukkan bahwa setelah dilakukan tindakan pembelajaran dengan menerapkan PBL berbantuan powerpoint: 1) terjadi peningkatan aktivitas pembelajaran sebesar 57% pada siklus I, dan 5% pada siklus II; 2) terjadi peningkatan hasil belajar sebesar 57,58% pada siklus I, dan 6,06% pada siklus II; 3) terjadi peningkatan ketuntasan belajar sebesar 36,37% pada siklus I, dan 12,12% pada siklus II; dan 4) peningkatan sikap dan keterampilan kerja sama kelompok sebesar 24,24% pada siklus II.